The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.1590/18069657rbcs20190044
|View full text |Cite
|
Sign up to set email alerts
|

Impact of agro-farming activities on microbial diversity of acidic red soils in a Camellia Oleifera Forest

Abstract: The production of Camellia oleifera (oil tea), typically planted in acidic red soils in southern China, is limited by low soil fertility. Agro-farming is one way to promote soil fertility by increasing organic matter and microbial communities. To understand the impact of agro-farming activity on soil fertility, three types of agro-farming, namely, raising laying hens under forest (RLH), cultivating Lolium perenne grass under forest (LPG), and maintenance of native grass (MNG), were employed in an oil tea farm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 57 publications
(58 reference statements)
3
19
0
Order By: Relevance
“…The dominant bacteria, Chloroflexi, Proteobacteria, Acidobacteria, Actinobacteria, and Planctomycetes, and fungi, Ascomycota and Basidiomycota, in the rhizosphere of C. yuhsienensis were similar to previous studies in C. oleifera rhizosphere or bulk soil [ 10 , 30 ], but a little different from the rhizosphere soil of Camellia sinensis [ 69 ]. These results indicated that nutrient utilization patterns of the plant might significantly alter microbial communities.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…The dominant bacteria, Chloroflexi, Proteobacteria, Acidobacteria, Actinobacteria, and Planctomycetes, and fungi, Ascomycota and Basidiomycota, in the rhizosphere of C. yuhsienensis were similar to previous studies in C. oleifera rhizosphere or bulk soil [ 10 , 30 ], but a little different from the rhizosphere soil of Camellia sinensis [ 69 ]. These results indicated that nutrient utilization patterns of the plant might significantly alter microbial communities.…”
Section: Discussionsupporting
confidence: 82%
“…Numerous studies have shown that seasonal variation strongly regulates soil physiochemical properties and microorganisms [ 10 , 59 , 60 , 61 , 62 ]. However, no studies have assessed the seasonal variation in soil properties and microbial communities in the rhizosphere of C. yuhsienensis .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations